The relationship between cultural intelligence and i-deals: Trust as a mediator and HR localization as a moderator. Issue 5 (7th November 2016) - Trong Luu, Tuan; Rowley, Chris
Abstract : Purpose: Cultural intelligence is the capacity to decode and harmonize with another culture for cultural synergy effects. This paper aims to examine whether cultural intelligence can activate idiosyncratic deals (i-deals) through trust as a mediator and HR localization as a moderator. Design/methodology/approach: Cross-sectional data from respondents from joint ventures or 100 per cent foreign-invested firms in Vietnam business setting, which were tested through the structural equation modeling, provide the evidence for the research model. Findings: Research results confirmed the positive effect of cultural intelligence on identity-based trust and knowledge-based trust, which in turn influence i-deals. HR localization was also found to play a moderating role on the relationship between identity-based trust or knowledge-based trust and i-deals. Originality/value: Cultural intelligence literature, from this study, is further deepened through its role as a trigger for the path from cultural intelligence to i-deals.